Spin-charge-lattice coupling in quasi-one-dimensional Ising spin chain CoNb2O6 - Nandi, M; Prabhakaran, D; Mandal, P (IOP Publishing, 2019)
Magnetization, magnetostriction and dielectric constant measurements are performed on single crystals of quasi-one-dimensional Ising spin chain CoNb$_{2}$O$_{6}$ at temperatures below and above the antiferromagnetic phase transition. Field-induced magnetic transitions are clearly reflected in magnetodielectric and magnetostriction data. Sharp anomalies are observed around the critical fields of antiferromagnetic to ferrimagnetic and ferrimagnetic to saturated-paramagnetic transition in both magnetodielectric and magnetostriction experiments. Detailed analysis of temperature and field dependence of dielectric constant and magnetostriction suggests that spins are coupled with lattice as well as charges in CoNb$_{2}$O$_{6}$. Below the antiferromagnetic transition temperature, the overall resemblance in anomalies, observed in various physical parameters such as magnetization, dielectric constant, magnetostriction and magnetic entropy change gives a deeper insight about the influence of spin configuration on these parameters in CoNb$_{2}$O$_{6}$.